Molecular Mechanisms of Differentiation of Murine Pro-Inflammatory γδ T Cell Subsets - Silva-Santos, Bruno; Serre, Karine (Frontiers in Immunology, 2013)
γδ T cells are unconventional innate-like lymphocytes that actively participate in protective immunity against tumors and infectious organisms including bacteria, viruses, and parasites. However, γδ T cells are also involved in the development of inflammatory and autoimmune diseases. γδ T cells are functionally characterized by very rapid production of pro-inflammatory cytokines, while also impacting on (slower but long-lasting) adaptive immune responses. This makes it crucial to understand the molecular mechanisms that regulate γδ T cell effector functions. Although they share many similarities with αβ T cells, our knowledge of the molecular pathways that control effector functions in γδ T cells still lags significantly behind. In this review, we focus on the segregation of interferon-γ versus interleukin-17 production in murine thymic-derived γδ T cell subsets defined by CD27 and CCR6 expression levels. We summarize the most recent studies that disclose the specific epigenetic and transcriptional mechanisms that govern the stability or plasticity of discrete pro-inflammatory γδ T cell subsets, whose manipulation may be valuable for regulating (auto)immune responses.